How efficient is the map of UBNs as a tool for social expenditure’s focalization? - Shack Y., Nelson (1999)
This paper is a contribution to the improvement of the social expenditure's focalization agenda. It focuses in government expenditures programs against poverty. To efficiently reach the goals, these programs must be included at the level of the universal and permanent programs. Once included these programs could provide a minimum set of equality opportunities, securing adequate nutrition, health, education, justice and housing services.   After a critical survey on methods of poverty measurement, we propose a New Poverty Map, which could be used to efficiently allocate government resources. This takes into account the consumption needs of the population, income inequality, and the severity of the poverty. In our results we emphasize that people participation is a key element favoring the communities’ development, the deepening of the democratic system and the strengthening of the accountability processes.